Synonyms Reflecting Objects and Phenomena of the Metaphysical World in the Translations of Sacred Texts from Arabic into English and Tatar - Akhmetzyanova, Dilyara R.; Gilemshina, Aysilu G. (Journal of History Culture and Art Research, 2017)
This paper analyzes the phenomenon of synonymy in translated texts in Russian and Tatar, with various existing and published translations of the Quran used as the main source. The primary goal of the study is to reveal the main regularities of the way synonyms function in the diachronic translations of the Quran into Russian and Tatar, as well as to follow the alterations in the vocabulary and stylistic norms of Russian and Tatar. Comparison between various translations allows shedding light on many of the peculiarities of the target language at the time the translation was completed and establishing the chronologic sequence of certain changes in the languages. The primary methods used in the study are the analysis of academic literature on the problem, consolidation of the prior research of synonyms in Russian and Tatar, studying text sources and dictionaries and comparison between the lexical units. The study shows that synonymic units found in the diachronic translations can be of varying degrees of equivalence. The most frequent in the diachronic translations of the Quran are the so-called partial synonyms, and this reflects the translators’ attempts to single out one specific lexical-semantic variant or a certain seme.